2017
DOI: 10.1177/0092055x16685373
|View full text |Cite
|
Sign up to set email alerts
|

“Why Did You Blend My Learning?” A Comparison of Student Success in Lecture and Blended Learning Introduction to Sociology Courses

Abstract: Introduction to Sociology at a large public university was taught in two separate formats, blended learning and lecture, during the same semester by the first author. While some similarities existed, the distinction was in delivery of course content. Additionally, the blended class had one-third less in-class time that was primarily devoted to active learning. In this quasi-experimental study, the researchers tested differences in learning using grades and pre-posttests. Although there were no statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 32 publications
3
31
0
1
Order By: Relevance
“…This research is in line with previous research (e.g. Luna & Winters, 2017;Warner, 2016) in showing that blended learning can contribute to enhanced pedagogy. The concerned stakeholders such as administrators, faculty members, or student representative should advocate the benefits of adopting blended learning.…”
Section: Pedagogical Implicationssupporting
confidence: 92%
See 3 more Smart Citations
“…This research is in line with previous research (e.g. Luna & Winters, 2017;Warner, 2016) in showing that blended learning can contribute to enhanced pedagogy. The concerned stakeholders such as administrators, faculty members, or student representative should advocate the benefits of adopting blended learning.…”
Section: Pedagogical Implicationssupporting
confidence: 92%
“…Similar positive results were reported in two recent studies (i.e. Luna & Winters, 2017;Warner 2016). Warner's (2016) study on blended learning that made use of short recorded lectures followed by online discussion forums showed that such discussions allowed students to take charge of their own learning; made learning easier and more productive through collaboration and discussion; increased students' satisfaction; and brought improvement in students' writing performance as they got exposure to others' ideas and learnt to ask good questions.…”
Section: Literature Reviewsupporting
confidence: 92%
See 2 more Smart Citations
“…Moodle can improve the learning process [9]. ICT-based learning with blended learning makes the learning process centered on students (student centered) because students are more active and effective compared to conventional learning [10]. Blended learning learning makes students collaborate with their peers, teachers, schools, and other parties involved so as to increase student success and satisfaction [11].…”
Section: Discussionmentioning
confidence: 99%